2016
DOI: 10.1063/1.4941985
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput and clogging-free microfluidic filtration platform for on-chip cell separation from undiluted whole blood

Abstract: Rapid separation of white blood cells from whole blood sample is often required for their subsequent analyses of functions and phenotypes, and many advances have been made in this field. However, most current microfiltration-based cell separation microfluidic chips still suffer from low-throughput and membrane clogging. This paper reports on a high-throughput and clogging-free microfluidic filtration platform, which features with an integrated bidirectional micropump and commercially available polycarbonate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…adhesive into the ring-shaped structure and the major aim was to prevent leakage during the filtration process. Compared to other microfluidic chips, [2][3][4][5][6][7][8][9][10][11][12][13][19][20][21] the onsite blood filtration could be realized with this device by inserting the tip of the plastic syringe into this device. The bonding technique, two-step injection and curing of UV adhesive, would ensure an efficient filtration process and no leakage would happen during the filtration process.…”
Section: Discussionmentioning
confidence: 99%
“…adhesive into the ring-shaped structure and the major aim was to prevent leakage during the filtration process. Compared to other microfluidic chips, [2][3][4][5][6][7][8][9][10][11][12][13][19][20][21] the onsite blood filtration could be realized with this device by inserting the tip of the plastic syringe into this device. The bonding technique, two-step injection and curing of UV adhesive, would ensure an efficient filtration process and no leakage would happen during the filtration process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a common electroporation instrument such as an optical tweezer will damage the cell membrane during the transfection [165]. DEP techniques have circumvented the research impediment by providing a high resolution of isolation and separation of target bio-particles directly from the whole blood and other biological fluid samples [126,173,174,175]. Furthermore, unlike optical tweezers, DEP provides a low applied voltage and an alternating current for gene transfection from DNA that can prevent cell membrane damage [165].…”
Section: Dep Applications In Biomedical Sciencesmentioning
confidence: 99%
“…[26] In 2016, Cheng et al demonstrated a clogging-free platform for cell separation from undiluted blood, which is highly susceptible to clogging. [123] They used a bidirectional micropump to enable reverse flushing of micropores to prevent clogging of the commercially available polycarbonate membranes. Their bidirectional flow strategy highlights the impact of oscillatory motion in clog prevention.…”
Section: Clog Mitigationmentioning
confidence: 99%